Fundamental of Entrepreneurship ENT300 Mushi Enterprise / Siti Rohaiyumi Kipli... [et.al] - Kipli, Siti Rohaiyumi; Mohd Mortadza, Fathin Hanani; Rambli, Norazeera Syuhaina; Bos, Mazalinawati; Wan, Valarie Aida (2016)
Name of the company: Our Company will be called as Mushi Enterprise Nature of the business: Our business is based on food service which is selling the sushi to customer Address : Our business will be operated at LG-73 Plaza Merdeka, Pearl Street, Sarawak, 93000 Kuching, Malaysia Factors in We choose this type of business because it can selecting the make a high profit as our food is new and proposed business unique Future prospects of: This business has good future prospects. This is because our product is differ from other Sushi and it's new in the market. In the market they only sell types of sushi that mostly their sushi topping is based on raw ingredient only. While our sushi topping is based on 'sambal' that symbolize Malaysia country.